A igreja católica no processo de formação da classe trabalhadora - Albuquerque, Ronald de Figueiredo e (2012)
The present work describes the process by which the Catholic Church turns its attention to society and commits itself to the poorest. This commitment helped organize the popular segments, while at the same time, it allowed a reflection on the action of the Catholic Church itself. This reflection has changed the political praxis of religious and lay people who came to see the Church as a privileged instrument of social and political change, since it is an institution present in every corner shaping the population in general. I stress also, the role of popular segments, which not only suffer the action of the Church, but exert back on it a critical role, capable of influencing sectors of the Catholic Church, causing them to review positions and define actions more relevant to the reality of the popular segments. In this work, I analyze the trajectory of the Catholic Church in Brazil, when, gradually, some segments of its hierarchy take part in the struggles of the people, revealing the processes of domination and submission in place, forcing an official position of the Church that ultimately impacts Vatican II. Afterwards, the Church, historically, becomes committed to the poor--it is the Church of the poor, as well defines the liberation theology. This commitment leads to the organization of the Basic Ecclesial Communities (BECs). These communities become more expressive politically, primarily, from the years of military dictatorship. This peculiarity makes some scholars believe that the political presence of the CEBs is a consequence of the closure of formal political spaces such as unions and political parties. The thesis that I defend, based on studies of the Diocese of Crateús, is that the BECs are meeting spaces that are transformed into spaces of social and political activities that the Church has taken control of since the 1950s. Crateús is a clear demonstration that communities are gathering spaces and, therefore, political spaces of active and critical speech in a church that stands open to talking to the people, encouraging them to participate in the actions defined in the communities. BECs are, as a result, spaces of political education that still reverberate in the action of popular strata. The methodology used was based on direct contact with the workers who participated in BECs with the 9 Church, priests, nuns, pastoral workers, union members and coordinators, through individual and group interviews, analysis of documents and books, participation in meetings and visits to some institutions created through the action of BEC members.